Use and outcomes of multivessel percutaneous coronary intervention in patients with acute myocardial infarction complicated by cardiogenic shock (from the EHS-PCI registry) - Bauer, Timm; Zeymer, Uwe; Hochadel, Matthias; Zahn, Ralf; Gitt, Anselm Kai (The American journal of cardiology, 2012)
The value of multivessel percutaneous coronary intervention (MV-PCI) in patients with cardiogenic shock (CS) and multivessel disease (MVD) is still unclear because randomized controlled trials are missing. Therefore, we sought to evaluate the impact of MV-PCI on in-hospital outcomes of patients with MVD presenting with CS: 336 patients with acute myocardial infarction complicated by CS and ≥70% stenoses in ≥2 major epicardial vessels were included in this analysis of the Euro Heart Survey PCI registry. Patients undergoing MV-PCI (n = 82, 24%) were compared to those with single-vessel PCI (n = 254, 76%). The rate of 3-vessel disease (60% vs 57%, p = 0.63) was similar in the 2 cohorts. Presentation with resuscitation (48 vs 46%, p = 0.76) and ST-segment elevation myocardial infarction (83 vs 87%, p = 0.31) was frequent in patients with MV-PCI and single-vessel PCI. Patients with ventilation were more likely to receive MV-PCI (30% vs 19%, p = 0.05). There was a tendency toward a higher hospital mortality in patients with MV-PCI (48.8% vs 37.4%, p = 0.07). After adjustment for confounding variables, no significant difference for in-hospital mortality (odd ratio [OR] 1.28, 95% confidence interval [CI] 0.72 to 2.28) could be observed between the 2 groups. Age (OR 1.41, 95% CI 1.13 to 1.77), 3-vessel disease (OR 1.78, 95% CI 1.04 to 3.03), ventilation (OR 3.01, 95% CI 1.59 to 5.68), and previous resuscitation (OR 2.55, 95% CI 1.48 to 4.39) were independent predictors of hospital death. In conclusion, MV-PCI is currently used in only 1/4 of patients with CS and MVD. An additional nonculprit PCI was not associated with a survival benefit in these high risk patients.